True blue through oxidation: a thiaazulenic heterophenoquinone as electrochrome - Intorp, Sebastian; Kushida, Soh; Rominger, Frank; Freudenberg, Jan; Hinkel, Felix Peter; Bunz, Uwe H. F. (Chemistry - a European journal, 2019)
A thiaazulenic quinone TAQ was synthesized and its optical and redox properties were investigated. The deep blue-colored compound is readily and reversibly reduced to the colorless anionic state. Electrochromic films were prepared and showed reversible switching behavior for the anodically coloring and NIR electrochromic material.